PTU-043 Diagnostic Yield and Safety of Small Bowel Capsule Endoscopy. (4th June 2013) - Houston, E; Rivera-Forrester, R; Haslam, N; Morris, A; Reid, P; Collins, P
Abstract : Introduction: Small bowel capsule endoscopy (CE) is a minimally-invasive, established tool for the detection of small bowel lesions. Methods: All capsule endoscopy reports from Jan 2007 to Aug 2012 performed at the Royal Liverpool University Hospital were reviewed. Results: A total of 311 examinations were performed during the period of review. Patients undergoing CE had a median age of 53 years (range 15 – 88) and a male:female ratio of 48.6%:57%. The commonest indication for examination was unexplained iron deficiency anaemia (IDA) (48.6%). Other indications included assessment for suspected Crohn's disease (23.5%), obscure overt GI blood loss (11.9%), polyposis syndrome (3.9%), diarrhoea (2.6%)and investigation of refractory coeliac disease (1.6%). The median gastric transit time was 19 mins (range 0 – 276 mins). The median small bowel transit time was 245 mins (range 61–533 mins). The capsule failed to reach the colon in 17.4% of cases. 41.8% of examinations were normal. The commonest finding in patients with IDA was angioectasia (19.9%). 59.5% of patients with obscure overt GI blood loss had positive findings. (Active bleeding (24.3%), Vascular lesion (5.4%), polyp (10.8%), NSAID enteropathy (2.7%), and gastritis (2.7%)). Crohn's disease was identified in 5.8% of all cases and in 13.8% of cases referred for assessment of suspected Crohn's disease. 4.6% of patients with IDA had findings consistent with Crohn's disease. Further investigation was advised in 36.7%. In 35.9% of those patients, the major abnormality identified for which a further procedure was required was located within the reach of a gastroscope. In those with IDA, gastroscopy was recommended in 22.7% of cases. Gastroscopy was recommended in a smaller proportion of patients (4.4%) having CE for other indications. A repeat procedure with bowel cleansing agents was required because of poor views in 1.6% of procedures. Capsule retention occurred in 2 of 186 patients (1.1%) for whom retention data was available. Prior small bowel imaging had not demonstrated a stricture in either case. Endoscopic removal of the capsule was successful in both patients. The cause of capsule retention was crohn's disease in one and NSAID enteropathy in the other. Conclusion: Adequate diagnostic images were obtained in > 98% of patients without the administration of bowel cleansing agents. The yield of positive findings from capsule endoscopy is high, but a significant proportion of lesions are within the range of a gastroscope, especially in patients with IDA. We recommend that patients undergo at least two gastroscopies prior to CE. CE is a safe procedure. Capsule retention was reported with a similar frequency to that reported in other case series. Patients should be advised that normal small bowel radiology may not exclude a significant stricture. Disclosure of Interest: None Declared